Basics of tuberculosis epidemiology - Cobelens, Frank (Henry Stewart Talks, 2013)
Global distribution of tuberculosis, Natural history, Risk factors for progression from latent infection to tuberculosis disease, Transmission, infection and re-infection, Quantifying the burden of tuberculosis in human populations, Impact of HIV on tuberculosis epidemiology
Archived at 2021/11/28